2017
DOI: 10.1111/vsu.12677
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct fixation with a Kirschner wire or a plate for lateral unicondylar humeral fracture stabilization

Abstract: Our results support the recommendation for adjunct fixation of comminuted lateral unicondylar humeral fractures with an epicondylar plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…To the authors’ knowledge this is not something specifically previously reported in the literature and is possibly attributed to the stability provided by the different adjunctive fixation modalities in addition to the TCS. The supracondylar K‐wire may not completely neutralize the rotational and shear forces that the fractured condyle must withstand during the healing period, whereas adjunctive plate fixation is biomechanically superior to supplemental K‐wire, and provides increased stiffness 34 . This should reduce cyclic stress on the screw which can often lead to implant failure 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors’ knowledge this is not something specifically previously reported in the literature and is possibly attributed to the stability provided by the different adjunctive fixation modalities in addition to the TCS. The supracondylar K‐wire may not completely neutralize the rotational and shear forces that the fractured condyle must withstand during the healing period, whereas adjunctive plate fixation is biomechanically superior to supplemental K‐wire, and provides increased stiffness 34 . This should reduce cyclic stress on the screw which can often lead to implant failure 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The supracondylar K‐wire may not completely neutralize the rotational and shear forces that the fractured condyle must withstand during the healing period, whereas adjunctive plate fixation is biomechanically superior to supplemental K‐wire, and provides increased stiffness. 34 This should reduce cyclic stress on the screw which can often lead to implant failure. 26 BCF may therefore have not suffered complications in this study due to all but one case being stabilized with adjunctive plates.…”
Section: Discussionmentioning
confidence: 99%
“…15,18,19,[24][25][26] Failure load (N) was defined as the maximum load recorded immediately prior to a sudden decrease in sustained load, which coincided with obvious visual construct failure. 25 At completion of destructive testing, the constructs were photographed and the specifics of failure documented for each construct. Mode of failure, including the location of bone fracture, plate bending or breakage, or screw bending, breakage or pullout was also recorded for each construct.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…More recently, the stability of this construct has been brought into question by the frequency of implant‐related complications when K‐wires are used to stabilise the epicondylar ridge fracture compared to when bone plates are used 5,6 . This concern was supported by cadaveric studies showing that stiffness, yield load and load to failure are all greater when bone plates rather than K‐wires are used in conjunction with a transcondylar bone screw 7 . As a result of these observations, recommendations have gravitated towards the use of epicondylar bone plates rather than K‐wires or pins, in combination with transcondylar bone screws, to manage these patients, 8 including when such fractures are treated in puppies 9 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 This concern was supported by cadaveric studies showing that stiffness, yield load and load to failure are all greater when bone plates rather than K-wires are used in conjunction with a transcondylar bone screw. 7 As a result of these observations, recommendations have gravitated towards the use of epicondylar bone plates rather than K-wires or pins, in combination with transcondylar bone screws, to manage these patients, 8 including when such fractures are treated in puppies. 9 However, little attention has been directed at whether these recommendations are appropriate across the entire spectrum of patients treated for these fractures and, in particular, whether there might be a different approach to the management of puppies compared with adult dogs.…”
Section: Introductionmentioning
confidence: 99%